Using Zebrafish to Study Collective Cell Migration in Development and Disease - Olson, Hannah M.; Nechiporuk, Alex V. (Frontiers in Cell and Developmental Biology, 2018)
Cellular migration is necessary for proper embryonic development as well as maintenance of adult health. Cells can migrate individually or in groups in a process known as collective cell migration. Collectively migrating cohorts maintain cell-cell contacts, group polarization, and exhibit coordinated behavior. This mode of migration is important during numerous developmental processes including tracheal branching, blood vessel sprouting, neural crest cell migration and others. In the adult, collective cell migration is important for proper wound healing and is often misappropriated during cancer cell invasion. A variety of genetic model systems are used to examine and define the cellular and molecular mechanisms behind collective cell migration including border cell migration and tracheal branching in Drosophila melanogaster, neural crest cell migration in chick and Xenopus embryos, and posterior lateral line primordium (pLLP) migration in zebrafish. The pLLP is a group of about 100 cells that begins migrating around 22 hours post fertilization along the lateral aspect of the trunk of the developing embryo. During migration, clusters of cells are deposited from the trailing end of the pLLP; these ultimately differentiate into mechanosensory organs of the lateral line system. As zebrafish embryos are transparent during early development and the pLLP migrates close to the surface of the skin, this system can be easily visualized and manipulated in vivo. These advantages together with the amenity to advance genetic methods make the zebrafish pLLP one of the premier model systems for studying collective cell migration. This review will describe the cellular behaviors and signaling mechanisms of the pLLP and compare the pLLP to collective cell migration in other popular model systems. In addition, we will examine how this type of migration is hijacked in various types of collectively invading cancer cells.